Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1074/jbc.ra118.003538
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of HIV-1 resistance to sifuvirtide, a clinical trial–approved membrane fusion inhibitor

Abstract: Host cell infection with HIV-1 requires fusion of viral and cell membranes. Sifuvirtide (SFT) is a peptide-based HIV-1 fusion inhibitor approved for phase III clinical trials in China. Here, we focused on characterizing HIV-1 variants highly resistant to SFT to gain insight into the molecular resistance mechanism. Three primary substitutions (V38A, A47I, and Q52R) located at the inhibitor-binding site of HIV-1's envelope protein (Env) and one secondary substitution (N126K) located at the C-terminal heptad repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 57 publications
(51 reference statements)
3
24
0
Order By: Relevance
“…Several N/CHR mutations also enhanced entry into cells bearing macaque receptors by a second transmitted Env strain, indicating that their effects were not strain specific. While N/CHR mutations have previously been identified that heighten fusogenic activity [45,46] and increase infectivity of cells expressing low levels of CD4 and CCR5 receptors [40,47], none have been shown to enhance entry of cells bearing macaque receptors. Many of the N/CHR mutations we identified also enhanced entry into cells bearing human CD4 and CCR5 receptors, but the magnitude of this effect was smaller than during infection of cells bearing macaque receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several N/CHR mutations also enhanced entry into cells bearing macaque receptors by a second transmitted Env strain, indicating that their effects were not strain specific. While N/CHR mutations have previously been identified that heighten fusogenic activity [45,46] and increase infectivity of cells expressing low levels of CD4 and CCR5 receptors [40,47], none have been shown to enhance entry of cells bearing macaque receptors. Many of the N/CHR mutations we identified also enhanced entry into cells bearing human CD4 and CCR5 receptors, but the magnitude of this effect was smaller than during infection of cells bearing macaque receptors.…”
Section: Discussionmentioning
confidence: 99%
“…N/CHR mutations enhanced entry into cells bearing macaque receptors by a second transmitted Env strain, indicating that their effects were not strain specific, but they did not confer a CD4 independent phenotype. While N/CHR mutations have previously been identified that heighten fusogenic activity (39, 40) and increase infectivity of cells expressing low levels of CD4 and CCR5 receptors (34, 41), none have been shown to enhance entry of cells bearing macaque receptors. Many of the N/CHR mutations we identified also enhanced entry into cells bearing human CD4 and CCR5 receptors, but the magnitude of this effect was smaller than during infection of cells bearing macaque receptors.…”
Section: Discussionmentioning
confidence: 99%
“…By adding the M-T hook structure to the PBD sequence, we previously generated several highly potent short-peptide fusion inhibitors, including MTSC22EK, HP23, and 2P23, which mainly target the deep pocket sites rather than the T20 resistance sites [20][21][22]. As noted, the resistance profiles of both the C34 derivatives and M-T hook-based short peptides were previously characterized by the in vitro selection of HIV-1 variants that were resistant to the inhibitors, and interestingly, the secondary N126K mutation was universally found to accompany with the diverse primary resistance mutations [23][24][25][26][27][28][29][30]. In the CHR sequence, Asn126 locates immediately at the downstream of the PBD sequence and it is a highly conserved residue among all the HIV-1, HIV-2, and even simian immunodeficiency virus (SIV) isolates (www.hiv.lanl.gov).…”
Section: Introductionmentioning
confidence: 94%
“…The expression and processing profile of HIV-1 gp160 were determined by a capture enzyme-linked immunosorbent assay (ELISA) as described [25]. Briefly, the wells of an ELISA plate were coated with a sheep anti-gp120 antibody (D7324) at 10 µg/mL and blocked by 3% bovine serum albumin (BSA).…”
Section: Capture Elisamentioning
confidence: 99%
See 1 more Smart Citation